Online cathodal transcranial direct current stimulation to the right homologue of Broca's area improves speech fluency in people who stutter. Issue 2 (11th December 2018) - Yada, Yasuto; Tomisato, Shuta; Hashimoto, Ryu‐ichiro
Abstract : Aim: Previous functional imaging studies demonstrate that people who stutter (PWS) exhibit over‐ and under‐activation of Broca's and Wernicke's areas and their right hemisphere homologues when speaking. However, it is unclear whether this altered activation represents the neural cause of speech dysfluency or a secondary compensatory activation in PWS. To clarify the functional significance of the altered activation pattern in classic language areas and their right homologues, we examined whether the severity of stuttering was affected when the activation of these areas was modulated by brain stimulation. Methods: While PWS read passages aloud, we applied transcranial direct current stimulation (tDCS) using electrode montages that included an anodal or cathodal electrode placed over one of the language areas and its right hemisphere homologue, with the second electrode placed over the contralateral supraorbital region. Each participant underwent both anodal and cathodal tDCS sessions, each of which included a sham stimulation. Effects of stimulation polarity and electrode location on the frequency of stuttering were analyzed. Results: We observed a significant interaction between polarity and location on the frequency of stuttering. Follow‐up analyses revealed that a tDCS montage including the cathodal electrode over right Broca's area (RB) significantly reduced the frequency of stuttering. Conclusion: The results indicated that stuttering severity was ameliorated when overactivation in RB was reduced by tDCS. This observation further suggests that speech dysfluency in PWS may be caused either by functional alteration in RB or by abnormal activation in speech motor control areas that are connected with RB.